Refleksje Hannah Arendt o „banalności zła” w reportażu „Eichmann w Jerozolimie” - Brzezińska, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
This article presents an analysis of the attitudes and contextualizes the conduct of Adolf Eichmann—the German Obersturmbannführer, executor of the Final Solution to the Jewish Question, whose trial, held in Jerusalem in 1961, became the basis for the book Eichmann in Jerusalem, written by the German philosopher Hannah Arendt. This study included a phrase concerning Eichmann’s behavior—the “banality of evil,” which, like the book itself, caused and constantly provokes numerous controversies, not only of a philosophical and existential nature, but also because of the way it is understood. The present article is an attempt to look at this issue from many angles, as well as to point out the avenues of criticism of the perception of A. Eichmann himself, whom Hannah Arendt describes as a cog in the German extermination machine. This perspective of the researcher, repeatedly questioned, has continued to provoke reflection for several decades. The question arises as to whether it is possible for a man who contributed to the extermination of more than 9 million Jews to be able to justify his acts only by the orders of his superiors he followed.
Keywords: nazizm; „banalność zła”; odpowiedzialność karna; „ostateczne rozwiązanie”